Milo and the magical stones - Pfister, Marcus; Martens, Marianne (New York : North-South Books, 1997)
A mouse discovers an extraordinary stone that can bring delight or disaster to the world. Halfway through, the book splits into two sections, each offering a different ending.
"A book with two endings"--Cover.
Keywords: Toy and movable books -- Juvenile fiction; Mice -- Juvenile fiction; Plot-your-own stories -- Juvenile fiction; Decision-making -- Juvenile fiction; Conservation of natural resouces -- Juvenile fiction; Mice -- Fiction; Decision making -- Fiction; Conservation of natural resources -- Fiction